Simulation of the Filling Capability in Vane Pumps - Massimo Rundo; Giorgio Altare; Paolo Casoli (Energies, 2019)
In positive displacement pumps, the main volumetric loss at high speed is due to the incomplete filling of the variable volume chambers. The prediction of the limit speed and of the maximum flow rate delivered by a pump can be obtained only through Computational Fluid Dynamics (CFD) simulations, since the shape, the orientation, and the movement of the chambers with respect to the inlet volume must be considered, along with the non-uniform distribution of the gaseous phase, due to the dissolved air release. In this paper, the influence of different geometric parameters on the filling of a vane pump has been investigated through the commercial software PumpLinx®. At first, a model of a reference pump has been created and validated with different configurations of the suction flow area, then a simplified model has been used for assessing the influence of the geometry of the rotating assembly. It was found that a pump with a low ratio between the axial thickness and the diameter has a higher volumetric efficiency if the chambers are fed from one side only. Opposite behaviors were found in the case of pumps with small diameters and high thicknesses. Moreover, the filling could be improved by increasing the number of chambers, and by reducing the diameter of the rotor, even only locally.